078 Deep brain stimulation (DBS) for dyskinetic cerebral palsy: a pilot study. Issue 6 (24th May 2018) - Duma, Stephen R; Mahant, Neil; Ha, Ainhi; Kim, Samuel; Phu, Amy; Stewart, Kirsty; Waugh, Mary-Clare; Wolfe, Nigel; Russell, Dale C; Owler, Brian; Krause, Martin; Fung, Victor SC
Abstract : Introduction: Deep brain stimulation (DBS) targeting the internal segment of the globus pallidus (GPi) is effective for several forms of dystonia, particularly idiopathic isolated dystonia. DBS may also be helpful for some causes of chorea and other hyperkinetic disorders. A minority of people with cerebral palsy (CP) have dystonia or choreoathetoid movements (labelled dyskinetic CP). Treatment options to improve function for this group are limited. We aimed to investigate whether DBS is effective in reducing symptoms and improving function in dyskinetic CP. Methods: This study was a randomised, placebo-controlled, double-blinded, crossover trial. Four participants (2M:2F, aged 11–48 year) with dyskinetic CP were included between 2010–2011. Participants underwent GPi DBS implantation and were randomised to active or sham stimulation for 3 months, following which their DBS stimulation was switched for a further 3 months. The Bourke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) was used to rate the severity of dystonia at baseline, 3 months after initial treatment; and 3 months after crossover treatment. The study was terminated early due to slow recruitment. Results: One participant had a reduction in BFMDRS score with active stimulation; this participant was the oldest and had the mildest BFMDRS score. The remainder of the participants had either no change or a slight increase in BFMDRS score. Despite this, in longer-term follow-up, 3 participants reported symptomatic improvement and continue active DBS treatment 7–8 years post-surgery. Conclusion: We did not identify a benefit of GPi DBS for dyskinetic CP in our randomised controlled trial. However, 3 participants have had symptomatic improvement on long-term follow-up, consistent with other reports of benefit with GPi DBS. Limiting factors of the study include small sample size, participant heterogeneity and study design. It was noted that the final (efficacious) stimulation parameters required open label programming to achieve and were outside of those permitted by the protocol.